Instagram-Based Digital Marketing Strategy to Enhance Engagement and Follower Growth in a Nascent Coffee Shop SME: A Case Study from Kediri - Niluh Komang Kusuma Yasari; Esti Nurwulan; Prabu Nurdin Prayogonegoro; Yanik Febriyani; Sudarmiatin Sudarmiatin; Ruly Wiliandri (Komunitas Dosen Indonesia, 2026)
Intensifying competition within the independent coffee shop industry has compelled nascent small and medium-sized enterprises in secondary Indonesian cities to adopt structured digital marketing strategies to build brand awareness efficiently. Nevertheless, research examining how resource-constrained micro-enterprises can leverage Instagram to accelerate engagement growth and follower acquisition in non-metropolitan markets remains scarce. This study analyzes the effectiveness of Instagram-based digital marketing strategies, particularly content scheduling optimization and local influencer collaboration, at Fase Coffee, a newly established coffee shop in Kediri, East Java. A qualitative case study approach was employed, drawing on Instagram insight data collected through observation, in-depth interviews, and documentation from February to April 2026. Data were analyzed descriptively and interpretively by integrating Temporal Consumption Theory, Attention Economy Theory, Customer Engagement Theory, and Source Credibility Theory. Findings indicate that uploading content on Tuesdays, Wednesdays, and Sundays between 18.00 and 21.00 Western Indonesia Time consistently produced higher audience engagement. Local influencer collaboration demonstrably expanded content reach, achieving 2,499 views on a single post. Total impressions grew 217 percent from 12,000 in February to 38,000 in April, while followers increased from 153 to 287. This study demonstrates that influencer geographic relevance and data-driven content scheduling timing are independent strategic variables determining the effectiveness of organic marketing for micro-enterprises in non-metropolitan markets.